Relasi Demokrasi, Kekuasaan, dan Politik Hukum dalam Pemilihan Presiden dan Wakil Presiden Tahun 2019 - Burhani, Muhammad Luthfi Munzir Abdul Muthalib; Jendrius, Jendrius; Syahrizal, Syahrizal (Universitas Medan Area, 2019)
General Election is a means of popular sovereignty that is held directly, publicly, freely, secretly, honestly and fairly (overflowing and fair). Law Number 7 of 2017 concerning General Elections as a product of legal politics does not place candidates who will fight in the Election of President and Vice President in 2019 in a fair and equal position. Incumbents benefit more so that they create ambiguous interests. Thus, substantial justice as part of real democracy tends to be ignored for the sake of power. This paper uses a literature study approach. This interest bias can be avoided by placing regulations equally and fairly. There needs to be a revision of Law No.7 of 2017 so that the incumbent who will run again as a presidential candidate or vice president resigns from his position. This is to safeguard the principle of justice in the 2019 electoral process and to keep ambiguous interests from being used to gain power.